2022
DOI: 10.3390/economies10030070
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Growth Rate and ROE Analysis: An Applied Study on Saudi Banks Using the PRAT Model

Abstract: This study aims at testing the effect of the components of the PRAT model and the basic model developed by Robert Higgins on the rate of sustainable growth by applying them to a sample of Saudi banks during the period of 2010–2019. Regarding the PRAT model, as Higgins explained, it is that detailed model measuring the sustainable growth rate by profit margin (P), retention rate (R), asset turnover (A), and leverage (T). To test the relation between the study variables, multiple regression analyses were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
0
6
1
1
Order By: Relevance
“…However, the results contradict the findings by Thuranira (2014) who indicated that internal equity has no significant impact on profitability. The results also differ with Altahtamouni, et al (2022) who indicated that retained earnings have no significant impact on the profitability of Saudi banks. To test whether bank size moderating the nexus between internal equity capital on financial performance of lower tier commercial banks in Kenya, the results are as indicated in table 8.…”
Section: Hierarchical Multiple Linearcontrasting
confidence: 89%
“…However, the results contradict the findings by Thuranira (2014) who indicated that internal equity has no significant impact on profitability. The results also differ with Altahtamouni, et al (2022) who indicated that retained earnings have no significant impact on the profitability of Saudi banks. To test whether bank size moderating the nexus between internal equity capital on financial performance of lower tier commercial banks in Kenya, the results are as indicated in table 8.…”
Section: Hierarchical Multiple Linearcontrasting
confidence: 89%
“…The ratio of banks like ROE, ROA, and NIMR represents whether the profitability condition or financial position is sufficiently sound in terms of ensuring the sustainability position of the banks. In an application, return on equity and retained earnings affect the sustainable growth rate of banks [30]. Therefore, the outcomes of our paper also must be helpful to ensure the sustainable financial condition of the banking system.…”
Section: Introductionmentioning
confidence: 95%
“…This is because corporate disclosure, if done in a conscious and truly effective manner, reduces the risk and uncertainty about performance and potential risks associated with the company. Finally, companies with a high level of ESG are expected to have higher growth potential because they have a long-term vision and take a more strategic approach to decision-making (Altahtamouni et al , 2022; Chatterji et al , 2016). While these results do not have a positive impact on corporate value in the short term, they can have a significant impact on the sustainability of shareholder value.…”
Section: Literature Reviewmentioning
confidence: 99%